A Multi-Agent System for Domain Information Discovery and Filtering - Braga, Regina M. M.; Costa, Marcelo N.; Werner, Cláudia M. L.; Mattoso, Marta (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2000: Anais do XIV Simpósio Brasileiro de Engenharia de Software, 2000)
The main objetive of Domain Engineering is to provide domain information that helps the specification of domain applications. Several Domain Engineering methods organize domain information using different representations, which can be stored in various formats. This paper presents a navigation agent system that provides heterogeneous/distributed acess to domain information. Ideas drawn from the field of autonomous agents, user modeling, hypermedia, and mediation are combined into a multi-agent system responsible for discovery and filtering of domain information. An evolutionary model of the user interests and domain ontology are some of the underlying concepts of the agent system that helps users to identify relevant domain information.